O uso de atividades educativas para empoderamento de estudantes em relação à saúde bucal - Oliveira, Garithuzy Macedo (2019)
Education and information on oral health care have been highlighted because of the influence on attitude change, behavior, empowerment, and the development of healthy habits. Lack of knowledge about oral hygiene care is a factor to be considered, since information, even if available, does not reach all social classes and is difficult to understand in order to produce knowledge and autonomy in relation to care Cheers. Faced with this problem, this research proposes to evaluate the impact of educational activities on the empowerment of children of a public school in relation to oral health and hygiene, through a descriptive and exploratory, qualitative approach, with children enrolled in the Municipal School Santa Luzia, located in the Municipality of Araguaína, Tocantins, Brazil. In the study, a questionnaire on health and care with oral hygiene was carried out, educational activities were carried out, with a focus on health and care with oral hygiene, construction of educational material on oral health and reapplication of the questionnaire. Through the participatory approach, there was a change in the behavior of children regarding oral health in the categories of oral health knowledge, perception of oral health and changes in habits of oral hygiene after participation in health education activities. In this way, the reorientation of practices, in the sense of making them more engaging, through dialogue, problematization and the active participation of all involved achieve better results empowering the subjects.